2020
DOI: 10.7127/rbai.v13n5001125
|View full text |Cite
|
Sign up to set email alerts
|

Ambiência Agrícola E Estresse Salino Em Mudas

Abstract: O quiabeiro (Abelmoschus esculents (L.) Moench), é uma hortaliça anual cultivada em regiões tropicais, destacando a variedade Santa Cruz 47 que é bastante difundida no Brasil. O objetivo deste trabalho foi avaliar a influência do estresse salino na emergência e no crescimento inicial de plântulas de quiabo cv. Santa Cruz 47 cultivadas em diferentes substratos e ambientes. O delineamento utilizado foi inteiramente casualizado (DIC), em parcelas subsubdivididas, sendo a parcela representada pelos ambientes: T1-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
3
11
0
2
Order By: Relevance
“…Similar results for seedling height were found by Goes et al (2019) working with okra seedlings and by Costa et al (2015) working with Dipteryx alata Vog.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results for seedling height were found by Goes et al (2019) working with okra seedlings and by Costa et al (2015) working with Dipteryx alata Vog.…”
Section: Resultssupporting
confidence: 84%
“…As shown in figure 1A, the leaf area values were statistically higher for the seedlings produced in the black screen. The black screen possibly has a capacity to provide greater thermal comfort when compared to full sun and other screens, causing the plants to have a lower energy expenditure and consequently have a higher growth (Goes et al, 2019). The black screen was statistically better than the others for plant height (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this study, Cavalcante et al ( 2008) irrigated the 'pitaya' crop with high-salinity water and found a smaller cladode diameter in a greenhouse. However, Goes et al (2019), evaluating the influence of saline stress on okra seedlings grown in different environments (structure with 50% shading and full sunlight), did not observe any significant effect for this variable.…”
Section: 0mentioning
confidence: 74%
“…This effect may be related to the smaller amount of macropores provided by the manure and consequently the lower water absorption, resulting in lower seed imbibition. On the other hand, biochar is composed of larger particles with lower degree of compaction, generating greater water absorption and favoring emergence (Lisboa et al, 2018;Goes et al, 2019).…”
Section: Resultsmentioning
confidence: 99%